Autonomous Vehicles – a New Challenge to Human Rights? - Iwan, Dominika (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2019)
New technologies, as autonomous vehicles are, disrupt the way people exist, and con-sequently with human rights. Research devoted to artificial intelligence and robotics moves freely and the destination, for the time being, is unknown. This is the reason why special attention should be paid to the ethics of these branches of computer science in order to prevent the creation of a crisis point, when human beings are no longer neces-sary.. The aim of this paper is to examine whether such development is a new challenge to human rights law and what happens when an autonomous vehicle drives an autono-mous human being. The paper also mentions the desirable level of human control over the machine so that human dignity, from which human rights originate, is preserved.